Status and prospects of tribology in the Republic of Korea - Hae-Jin Kim; Yong Hoon Jang; Dae-Eun Kim (Friction)
Tribology has played an essential role in the advancement of technology and the development of economies all over the globe. As such, a significant part of the Korean industry has benefitted from design solutions and remedies that stem from tribological considerations. Republic of Korea has grown tremendously in the traditional application fields of tribology, such as automotive, manufacturing, heavy industry, shipbuilding, and electronics, over the last few decades. Apart from these traditional fields, tribology has been contributing significantly to emerging industries related to energy, environment, and biotechnology in the Republic of Korea. In this paper, the status and prospects of tribology in the Republic of Korea are presented. The history and activities of the Korean Tribology Society (KTS) are described along with a review of the research works of selected Korean tribologists. Considering the great relevance of friction, wear, and lubrication issues in future sustainability, efforts in tribology will continue to expand in parallel with technology and economic development in the Republic of Korea and around the globe.